Implementation Education Maintenance Rope Center In NY. S G1P1A0 Post Sectio Caesarea With Knowledge Deficit in Dewi Sartika Room, RSUD Arjawinangun Cirebon - Nengsih Yulianingsih; Tasya Widia Putri (International Journal Of Health Science, 2025)
The postpartum period, which typically lasts for six weeks, is crucial for the recovery of the mother after childbirth. Special care is required during this time to ensure the health and well-being of both the mother and the baby. Cesarean section (CS) deliveries require more intensive care due to the increased risk of complications. Additionally, newborns are particularly vulnerable to health risks, including infections of the umbilical cord. Proper care of the umbilical cord is essential to prevent infections that can harm the baby’s health. The objective of this study is to implement education on umbilical cord care for patients experiencing nursing problems related to knowledge deficits regarding umbilical cord care. This scientific paper uses a descriptive case study design, involving one patient (US) as the subject, and data was collected through interviews and observations. The results of the assessment revealed that the patient had limited knowledge about proper umbilical cord care. After two educational sessions, the patient’s understanding improved. On the first day, the patient was able to answer 7 out of 10 questions related to umbilical cord care, while on the second day, the patient could answer 10 questions correctly, demonstrating a significant increase in knowledge. In conclusion, education on umbilical cord care proved effective in improving the patient’s knowledge, although further reinforcement is necessary. More interactive media could be utilized in future interventions to enhance understanding and ensure optimal care for the newborn. These findings underscore the importance of providing targeted education to new mothers to prevent potential health risks to their babies.